2021
DOI: 10.1017/jgc.2021.10
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and wellbeing as predictors of students’ academic achievement: evidence from a developing country

Abstract: The COVID-19 pandemic has deepened the effects of socioeconomic status (SES) and wellbeing (WB) on students’ academic achievement, particularly in developing countries; thus, it becomes necessary to understand the nature of these concurrent relationships. This study aimed to explore the relationships between SES, WB and academic achievement, based on the data from the Programme for International Student Assessment (PISA) in 2018 within the Turkish context. In this cross-sectional study, we used hierarchical mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 63 publications
(85 reference statements)
1
9
0
1
Order By: Relevance
“…One approach examines well-being as a means or source of successful learning and academic achievement. This approach is supported by international studies that show positive effects of subjective well-being on self-confidence, curiosity, and openness to new situations (Cefai & Spiteri 2021;Erdem & Kaya 2021;Lavis & Robson 2015;García Bacete et al 2014;Andresen, 2010) and thus on important preconditions of learning processes. Since 2015, the comparative PISA studies have included student's well-being in their surveys.…”
Section: Child Well-being In Educational Researchmentioning
confidence: 84%
“…One approach examines well-being as a means or source of successful learning and academic achievement. This approach is supported by international studies that show positive effects of subjective well-being on self-confidence, curiosity, and openness to new situations (Cefai & Spiteri 2021;Erdem & Kaya 2021;Lavis & Robson 2015;García Bacete et al 2014;Andresen, 2010) and thus on important preconditions of learning processes. Since 2015, the comparative PISA studies have included student's well-being in their surveys.…”
Section: Child Well-being In Educational Researchmentioning
confidence: 84%
“…Previous studies published in this country have reported that socioeconomic status is significantly associated with various developmental aspects, such as cognitive level [ 44 , 45 ] and visual–motor skills [ 15 ]. Indeed, parental employment and their financial involvement in their children’s learning were significantly associated with children’s cognitive levels [ 46 ], reading interests [ 47 ], and academic achievements [ 48 ], contributing positively to children’s development.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, many researchers state that home educational resources are highly correlated to students' achievement (Boulifa & Abdelali, 2022;Çoban & Kamış, 2019;Kılıç Depren et al, 2017). In addition, home educational resources are highly correlated to students' socio-economic and cultural status as well (Erdem & Kaya, 2021;Munez et al, 2021). Besides, in Information and Communication Technology (ICT) Usage survey conducted by TUİK, it is revealed that %85 of people has an internet connection in Turkey and 62% of them had a fixed broadband (ADSL, cable, optic fibre, etc.)…”
Section: Discussionmentioning
confidence: 99%